Medical barriers to contraception. - Huamán, Moisés (2015)
Worldwide, the increased prevalence of contraceptive use (AC) and the strengthening of family planning programs (PF) is observed; However, hundreds of millions of couples-more than 50% in the underdeveloped countries do not have access to family planning services despite wanting to, with the consequent unwanted pregnancy, illegal abortion and maternal death 2.4, 5.10. At present, it is considered as the primary goal of the PF improving reproductive health of couples, improve the quality of life and promote free and shapely choice of birth control, if requiere2,9,12. There are  many barriers that prevent or alter the access and quality of care in PF.